Spatial assessment of ecosystem functions and services for air purification of forests in South Korea. Issue 63 (September 2016) - Song, Cholho; Lee, Woo-Kyun; Choi, Hyun-Ah; Kim, Jaeuk; Jeon, Seong Woo; Kim, Joon Soon
Highlights: Ecosystem services and ecosystem function have not been clearly distinguished. Natural functions, environmental services, and environmental social services can be applied. NF, ES, and ESS approach showed various according to environmental and social conditions. Differences in NF, ES, and ESS are important factors for the decision-making process. Abstract: Ecosystem functions can be understood as the quantified amount of an ecosystem's role in a natural process, while ecosystem services are the requantification of the ecosystem functions by factoring in environmental conditions and human needs based on social perspectives. In this study, differences between ecosystem functions and services were presented in terms of air purification of a forest ecosystem. Forest volume growth was employed to quantify the pollutant absorption capacity of a forest and was indicated by the natural functions (NF) for air purification by a forest ecosystem. Forest ecosystem services can be requantified from the forest functions by adding the air pollutant and population densities. Air pollutant density was applied to the assessment of the environmental services (ES) of forest ecosystems. Furthermore, the environmental social services (ESS) of forest ecosystems were assessed by including population density considerations. We simulated differences in NF, ES, and ESS in relation to pollutant and population density; while NF was spatially quantified without a close relationship to air pollutant and population density, ES and ESS reacted to environmental and social condition more sensitively. These results imply that the ecosystem services of forest resources for air purification are high where the pollutant and population densities are high, while the ecosystem functions of forest resources for air purification depend solely on forest conditions and not on the density changes of air pollutants and population. This study suggests that the differences in NF, ES, and ESS are important factors to be understood and considered in the decision-making process for ecosystem services. When considering human needs and surrounding environmental conditions, the results suggest that decision makers should utilize the ES and ESS concepts, which reflect both population and pollutant density along with additional human-related factors.